FISS: A factor based index of systemic stress in the financial system - Tibor Szendrei; Katalin Varga (Magyar Nemzeti Bank, 2017)
Tracking and monitoring stress within the financial system is a key component of macroprudential policy. This paper introduces a new measure of contemporaneous stress: the Factor based Index of Systemic Stress (FISS). The aim of the index is to capture the common components of data describing the financial system. This new index is calculated with a dynamic Bayesian factor model methodology, which compresses the available high frequency and high dimensional dataset into stochastic trends. Aggregating the extracted 4 factors into a single index is possible in a multitude of ways but averaging yields satisfactory results. The contribution of the paper is the usage of the dynamic Bayesian framework to measure financial stress, as well as producing the measure in a timely manner without the need for deep option markets. Applied to Hungarian data the FISS is planned to be a key element of the macroprudential toolkit.
Keywords: G01; G10; G20; E44; 330; Systemic stress; Financial Stress Index; Dynamic Bayesian Factor Model; Financial System; Macroprudential Toolkit